2022
DOI: 10.1155/2022/8321596
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Index of Nutritional Quality (INQ) and Obesity: Baseline Data of Kharameh Cohort

Abstract: Obesity is an increasing problem that can lead to noncommunicable diseases. The role of dietary factors on one’s obesity is confirmed in many studies. One nutritional approach that can be used for assessment of the foods and diets is the Index of Nutritional Quality (INQ). Our study is aimed at exploring the association between INQ and obesity. Our hypothesis is that enriched and high-quality diets reduce the risk of overweight or obesity. This study was carried out on 6248 overweight and obese participants, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“… Jalali et al. [ 14 ] (2022) Iran Prospective cohort 6248 adults aged 40–70 in Kharameh 130-item FFQ Normal weight %RDA: 112 ± 51% Overweight %RDA: 124 ± 52% Obese %RDA: 131 ± 56% Inverse association between risk of obesity and vitamin C intake Park [ 15 ] (2023) Korea Hospital-based cohort 58,701 adults aged >40 y from a large city hospital 106-item semiquantitative FFQ Male, low insulin resistance 107 ± 0.46 Male, high insulin resistance 106 ± 1.22 Female, low insulin resistance 105 ± 0.32 Female, high insulin resistance 99.1 ± 1.22 Vitamin C intakes above 100 mg are protective against insulin resistance. Hantikainen et al.…”
Section: Vitamin C Intakes In Participants With Overweight or Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“… Jalali et al. [ 14 ] (2022) Iran Prospective cohort 6248 adults aged 40–70 in Kharameh 130-item FFQ Normal weight %RDA: 112 ± 51% Overweight %RDA: 124 ± 52% Obese %RDA: 131 ± 56% Inverse association between risk of obesity and vitamin C intake Park [ 15 ] (2023) Korea Hospital-based cohort 58,701 adults aged >40 y from a large city hospital 106-item semiquantitative FFQ Male, low insulin resistance 107 ± 0.46 Male, high insulin resistance 106 ± 1.22 Female, low insulin resistance 105 ± 0.32 Female, high insulin resistance 99.1 ± 1.22 Vitamin C intakes above 100 mg are protective against insulin resistance. Hantikainen et al.…”
Section: Vitamin C Intakes In Participants With Overweight or Obesitymentioning
confidence: 99%
“…In a study conducted on a group of 126 overweight and obese Australian adults, there was a weak inverse correlation between BMI and vitamin C intake ( P = 0.2) [ 33 ]. In a population study from Kharameh province in Iran, data from 6248 participants showed an inverse association between vitamin C adequacy and risk of obesity [ 14 ]. Moreover, in Iran, the vitamin C intake of 812 patients with a BMI >25 attending a medical center was compared with 793 normal-weight subjects selected from their caregivers.…”
Section: Vitamin C Intakes In Participants With Overweight or Obesitymentioning
confidence: 99%